Silicon-Tethered Frameworks as Directing Groups for Carbon–Carbon and Carbon–Heteroatom Bond Formation - Usman, Muhammad; Zhang, Xiao-Wen; Liu, Wen-Bo (Synthesis, 2019)
Recent advances in the use of silicon-tethered frameworks as directing groups for the efficient construction of C–C, C–B, C–O and C–X (X = halogen) bonds are discussed in this short review. In addition, mechanistic insights are briefly discussed. Hence, the goal of this short review is to give an overview of the state of the art in this field, encompassing the reactivity, selectivity and efficiency of different processes.1 Introduction2 Carbon–Carbon Bond Formation2.1 Alkenylation2.2 Arylation2.3 Carbonylation3 Carbon–Boron Bond Formation4 Carbon–Oxygen and Carbon–Halogen Bond Formation5 Conclusion
Keywords: silicon; directing groups; C–H activation; transition-metal-catalyzed; C–C bond formation; C–heteroatom bond formation